Diet-microbe interactions in the gut : effects on human health and disease - Tuohy, Kieran; Del Rio, Daniele (London, UK : Elsevier, AP, Academic Press is an imprint of Elsevier, 2015)
Drawing on expert opinions from the fields of nutrition, gut microbiology, mammalian physiology, and immunology, this work investigates the evidence for a unified disease mechanism working through the gut and its resident microbiota, and linking many inflammation-related chronic diet associated diseases. State of the art post-genomic studies can highlight the important role played by our resident intestinal microbiota in determining human health and disease.
Includes bibliographical references and index.
Keywords: Gastrointestinal system -- Microbiology